PENINGKATAN PENDAPATAN ASLI DAERAH DALAM RANGKA OTONOMI DAERAH MELALUI POTENSI PAJAK DAN RETRIBUSI DAERAH DI KABUPATEN JAYAPURA - Parson Horota; Ida Ayu Purba Riani; Robert M. Marbun (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2017)
This study aims to analyze local revenue potential of Jayapura regency sourced from local taxes and levies, and identify the obstacles faced so that the contribution has not yet been effectively implemented and also the strategies to overcome the constraints in order to increase local revenue (PAD) through the potential of local taxes and levies. The research was using cluster sampling and simple random sampling methods. Data gathering technique in this research was interview, qusionary, and literature study. Type and a source of the data were primary and secondary data. The result of this research showed that the regional taxes and levies collection in Jayapura regency have not yet optimal, so that the contribution to PAD are still relatively low. Whereas this region has great tax potential, especially duties on land and building transfer (BPHTB), hotel tax, restaurant tax, parking tax, and non rock and metal taxes, which were not excavated optimally. Similarly local levies which has large potential, particularly the health service levy, disturbance permit, and garbage service. Hence, immediately effective strategy implementation to improve the charges result according to available potentials, that are able to encourage significantly PAD increase in the future. Keyword: local revenue (PAD), obstacle factors, local taxes and levies potential increasing strategies